2020
DOI: 10.1136/bmj.m1184
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of unrecognised myocardial infarction determined by electrocardiography or cardiac magnetic resonance imaging: systematic review and meta-analysis

Abstract: ObjectiveTo evaluate the prognosis of unrecognised myocardial infarction determined by electrocardiography (UMI-ECG) or cardiac magnetic resonance imaging (UMI-CMR).DesignSystematic review and meta-analysis of prospective studies.Data sourcesElectronic databases, including PubMed, Embase, and Google Scholar.Study selectionProspective cohort studies were included if they reported adjusted relative risks, odds ratios, or hazard ratios and 95% confidence intervals for all cause mortality or cardiovascular outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 66 publications
(32 reference statements)
1
30
0
1
Order By: Relevance
“…These results held true in two different multivariate models, and in an additional competing risk model with cardiovascular mortality and non-fatal MI considered separately, with hazard ratios persisting in the model suggesting the findings are robust. Furthermore, while the prognosis of silent perfusion defects on MRI has not been reported, that of unrecognized MI is well reported, with the current 2.4-fold risk in close agreement with that of a recent meta-analysis including 3018 patients in which there was a 3.2-fold risk of MACE in those with unrecognized MI [6].…”
supporting
confidence: 87%
“…These results held true in two different multivariate models, and in an additional competing risk model with cardiovascular mortality and non-fatal MI considered separately, with hazard ratios persisting in the model suggesting the findings are robust. Furthermore, while the prognosis of silent perfusion defects on MRI has not been reported, that of unrecognized MI is well reported, with the current 2.4-fold risk in close agreement with that of a recent meta-analysis including 3018 patients in which there was a 3.2-fold risk of MACE in those with unrecognized MI [6].…”
supporting
confidence: 87%
“…Hazard ratios (HRs) and 95% confidence intervals (CIs) adjusted for the maximal number of confounders were extracted for analysis. If relative risks (RRs) were reported, they were considered as approximate estimate for HRs and used for meta-analysis ( 18 ). In situations where outcomes were presented as odds ratios (ORs), data were converted to RRs for analysis, according to previously published method ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The meta-analysis included 30 studies with 253,425 participants and 1,621,920 person-years of follow-up, which is about prognosis of unrecognized MI determined by electrocardiography or cardiac MRI. Unrecognized myocardial infarction (UMI) by electrocardiography (ECG) or UMI by cardiac MR (CMR) is associated with an adverse long-term prognosis similar to that of recognized MI ( 48 ). Imaging evidence indicates a high prevalence of CAD in patients with T2DM; however, there is no standard for initiating CAD screening in the T2DM population, and it has been found that routine screening for CAD using computed tomographic coronary angiography (CTCA) should be considered for early detection of CAD in asymptomatic T2DM patients with diagnosed duration of T2DM >10.5 years and systolic blood pressure > 140 mmHg ( 49 ).…”
Section: Perspectivementioning
confidence: 99%